Sex Differences of Tooth Loss and Obesity on Systemic Markers of Inflammation. (August 2014) - Meisel, P.; Holtfreter, B.; Völzke, H.; Kocher, T.
Sex-specific differences in the incidence of periodontitis and tooth loss may be related to different phenotypes of obesity and their associations with low-grade inflammation. The aim of this study was to evaluate associations of adiposity and low-grade inflammation with tooth loss in men and women. Follow-up data of 2, 714 participants from the cohort of Study of Health in Pomerania were analyzed for anthropometric measures, periodontitis, tooth loss, C-reactive protein (CRP), and interleukin 6. Regression analyses were used to estimate the effect of obesity on tooth loss within sex strata. During the follow-up period, men lost more teeth in relation to their obesity status than did women. In contrast, there was a steeper increase in CRP levels across obesity levels in women as compared to men. Incidence rate ratio (IRR) of tooth loss associated with elevated CRP, however, was higher in men (IRR = 1.50; 95% confidence interval [CI]: 1.27, 1.77) than women (IRR = 1.18; 95% CI: 1.02, 1.37). Negative binomial regression with number of lost teeth as outcome revealed dose-response dependencies on body mass index and waist-to-hip ratio. Adjusted for covariates, the IRR of tooth loss associated with the third tertile of waist-to-hip ratio was 1.37 (95% CI: 1.04, 1.80) and 1.53 (95% CI: 1.14, 2.05) in men and women, respectively. Tooth loss related to CRP cutoff of 2 mg/L was significant in men (IRR = 1.33; 95% CI: 1.07, 1.66; p = .006) but not in women (IRR = 0.92; 95% CI: 0.73, 1.17; p = .689). This study suggests that both adiposity and subclinical inflammation affect tooth loss, with distinct differences between men and women. Obesity as a risk factor of tooth loss is particularly related to CRP in men but not in women.